Analisis Pengelolaan Penerimaan Dan Pengeluaran Kas Melalui Aplikasi Zahir Accounting Pada Apotek Ragasi Karawang Jawa Barat: Analysis of Cash Receipts and Expenditures Management Using the Zahir Accounting Application at Ragasi Pharmacy in Karawang, West Java - Hamida Asoka Putri; Dinar Riftiasari; Ahmad Ridwan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
In this era of globalization, the development of information technology has become a major catalyst in the transformation of the business world. Ragasi Pharmacy located in Karawang, West Java, is a business entity engaged in general trade, namely selling. Medicines and medical devices to consumers. And is one of the pharmacies that has implemented the Zahir system in the cash management process, especially in the aspects of cash receipts and disbursements. This study uses qualitative research using inductive analysis and is descriptive. Based on the facts and data obtained in the field, Ragasi Pharmacy in recording cash receipts and disbursements even though it has used the Zahir Accounting application. However, there are still some obstacles in its implementation. This is due to human resources who are less proficient in using Zahir Accounting. The Zahir Accounting application has been implemented at Ragasi Pharmacy Karawang to manage cash receipts and disbursements more efficiently, Each transaction is recorded clearly, Ragasi Pharmacy Karawang applies data verification and validation procedures before the transaction is saved. The success of implementing the Zahir system in cash management at Ragasi Pharmacy Karawang, The process of cash receipts and disbursements at Ragasi Pharmacy Karawang is carried out through structured steps.